STUDY OF STRENGTH CHARACTERISTICS OF CONCRETE, LOCAL EXPOSURE TO FIRE EXPOSURE - and (Municipal economy of cities (Technical science), 2013)
The results of testing of concrete and rebar, received higher temperature effects from the fire, made recommendations to strengthen the damaged concrete slab.